A Case Report on Lower Motor Neuron Lesion Secondary to Ramsay Hunt Syndrome - Sugandha Arya; Amreen Aijazuddin; Tanvi Sharma; Khushbu Lamba; Monika Tanwar; Nowsheen Yaqoob (New Advances in Medicine and Medical Science Vol. 7, 2023)
Ramsay Hunt syndrome is an illness brought on by the varicella zoster virus that is characterized by acute facial palsy, inner ear dysfunction, and herpetic eruptions on the auricle and external ear canal. Ramsay Hunt Syndrome can result in hearing loss, hence it is necessary to conduct otoscopic and audiometric tests. A case report of Ramsey Hunt Syndrome which is rare in dental clinic, often misdiagnosed and not extensively documented in literature. Early detection and intervention with antiviral and corticosteroids is essential in improving outcome of the disease. Here, we present a case report of Ramsay hunt syndrome causing lower motor neuron lesion.